Effectiveness of casein phosphopeptide-amorphous calcium phosphate and xylitol chewing gums on salivary pH, buffer capacity, and Streptococcus mutans levels: An interventional study - Krishnan Padminee; Saravanan Poorni; Davidson Diana; Dasarathan Duraivel; Manali Ramakrishnan Srinivasan (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of the study is to compare the anticariogenic effectiveness of Casein phosphopeptide- Amorphous Calcium phosphate (CPP-ACP) and xylitol chewing gums based on salivary pH, buffer capacity, and Streptococcus mutans levels. Materials and Methods: A group of twenty individuals in the age group of 18-25 years were randomly divided into two Groups A and B. Test arm A received xylitol gums and test arm B received CPP-ACP gums and they were instructed to use the gums thrice daily for 2 weeks. Unstimulated salivary samples were collected before they began the use of the gums for baseline values, 24 h after beginning the usage of chewing gums and at the end of 14 days. The samples were analyzed for pH, buffer capacity, and S. mutans levels. Results: A statistically significant reduction of salivary S. mutans levels, improvement in salivary pH, and buffer capacity were displayed in both groups 24 h and 14 days after the intervention when compared with baseline. Group B showed more statistically significant improvement in pH than group A after 24 h (P = 0.028) and at the end of 2 weeks (P = 0.041). Conclusion: CPP-ACP has better ability than xylitol in improving the pH of saliva. Both CPP-ACP and xylitol gums individually have remarkable ability in bringing down S. mutans levels while simultaneously improving the pH and buffer of saliva.